2020
DOI: 10.3390/su12072891
|View full text |Cite
|
Sign up to set email alerts
|

Technology Characteristics, Stakeholder Pressure, Social Influence, and Green Innovation: Empirical Evidence from Chinese Express Companies

Abstract: Over the past decade, the rapid development of e-commerce and express industries in China has resulted in huge environmental costs. Compared with manufacturing industries, the values of green innovation are less recognized in logistics industries. To promote the green practices in logistic enterprises, it is imperative to have a thorough understanding of the determinants of green innovation adoption. To this end, this paper performs an empirical investigation into the intentions to adopt green innovation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 97 publications
3
25
1
Order By: Relevance
“…This result is not consistent with the previous findings of many researchers, i.e., [7,8,28,36,[73][74][75]. Some of the recent studies from China [76], Korea [77], and Pakistan [78] have also found customer pressure as an insignificant predictor of e-commerce adopting intentions to green innovation. We propose here that the difference in the result is due to the difference in the context of developed and developing/emerging economies.…”
Section: Discussioncontrasting
confidence: 84%
“…This result is not consistent with the previous findings of many researchers, i.e., [7,8,28,36,[73][74][75]. Some of the recent studies from China [76], Korea [77], and Pakistan [78] have also found customer pressure as an insignificant predictor of e-commerce adopting intentions to green innovation. We propose here that the difference in the result is due to the difference in the context of developed and developing/emerging economies.…”
Section: Discussioncontrasting
confidence: 84%
“…This result differs from the previous findings of Banerjee et al [13] and Fraj-Andres et al [14], whose studies, conducted in the US and Spain, respectively, identified customer concern as a determining factor of corporate environmentalism. However, few recent studies from developing economies also found customers as inconsequential stakeholders [24,34,35]. We propose that the differing result can be explained by the differences in the two contexts.…”
Section: Discussionmentioning
confidence: 68%
“…Pedersen and Neergaard [33] argued that the green consumer is a rare and exclusive demographic. Seifert, Damert and Guenther [24], while studying the impact of hospital clients on the environmental management system of German hospitals, found customers as irrelevant stakeholders, and Zhang et al [34] found customers' pressures as an insignificant predictor of firms adopting intentions to green innovation in China. In addition, according to Raiz et al [35], customer priorities and their environmental guidelines are very different in emerging markets.…”
Section: Customer Concern and Corporate Environmentalismmentioning
confidence: 99%
See 1 more Smart Citation
“…This study fills the gap in investigating these constructs in the manufacturing and service industries to enrich existing GI practices and stakeholder pressure literature. Moreover, stakeholder pressure (customer) was examined for GI in third party logistic firms ( Chu et al, 2019 ), as well as in express companies ( Zhang et al, 2020 ), and in manufacturing firms ( Song et al, 2020 ). Those three studies were conducted in China’s context, which highlights the issue of conducting and focusing on the stakeholder pressure in the manufacturing and service industries of Pakistan being a developing economy in the initial stages of GI practices adoption ( Shahzad M. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%